2015
DOI: 10.15446/rsap.v17n4.30832
|View full text |Cite
|
Sign up to set email alerts
|

A influência do desenvolvimento sexual sobre as qualidades físicas básicas de meninos adolescentes

Abstract: Objective The objective of this study was to evaluate the effects of sexual maturation on anthropometric parameters and basic physical characteristics in male adolescents aged from ten to fourteen years old. Materials and Methods The biological age was studied through the evaluation of the stage of the external genitalia development. Other evaluated characteristics were: total body mass (MCT), stature, body mass index (BMI), bone age (IO), strength, speed, agility and aerobic power. Results The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
1
2
Order By: Relevance
“…Based on the premise that the maturational process is guided by the increase in the circulation of testosterone and estrogen hormones in boys and girls, respectively 21 , it would be reasonable to suppose that the more advanced stages of sexual maturation would present higher concentration of these hormones and, consequently, better performance in physical tests 24 . However, this premise was not supported by the results found in this study and diverges from previous studies, which have demonstrated that in more advanced maturational stages, physical performance is higher compared to individuals with delayed maturational stage 5,6 , as well as the hormonal concentration levels 25 . Vidal-Linhares et al 6 , observed a significant tendency to increase physical capacity in parallel with the advancement of the maturational stage in male adolescents.…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…Based on the premise that the maturational process is guided by the increase in the circulation of testosterone and estrogen hormones in boys and girls, respectively 21 , it would be reasonable to suppose that the more advanced stages of sexual maturation would present higher concentration of these hormones and, consequently, better performance in physical tests 24 . However, this premise was not supported by the results found in this study and diverges from previous studies, which have demonstrated that in more advanced maturational stages, physical performance is higher compared to individuals with delayed maturational stage 5,6 , as well as the hormonal concentration levels 25 . Vidal-Linhares et al 6 , observed a significant tendency to increase physical capacity in parallel with the advancement of the maturational stage in male adolescents.…”
Section: Resultscontrasting
confidence: 99%
“…However, this premise was not supported by the results found in this study and diverges from previous studies, which have demonstrated that in more advanced maturational stages, physical performance is higher compared to individuals with delayed maturational stage 5,6 , as well as the hormonal concentration levels 25 . Vidal-Linhares et al 6 , observed a significant tendency to increase physical capacity in parallel with the advancement of the maturational stage in male adolescents. When verifying the performance of the explosive strength of upper and lower limbs of young volleyball players, higher performance was observed in adolescents of both genders with accelerated maturational stage in relation to their pairs with delayed maturation, using a model that estimates bone age.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation